(untitled) (Clinical Sociology Review, 2023)
This article posits that clinical sociologists have ideal expertise to serve courts as a Guardian ad Litem. It explains what these court appointed representatives provide the court, their qualifications, and how they can advocate for the best interests of children in divorce, custody, shared-time, and other caregiving situations. Often decisions are made by judges with a adult-focused legal lens. Clinical sociologists have a background in both macro and micro issues that impact the wellbeing of children. They are able to contribute and integrate their scholarly and practical knowledge to make better informed decisions that the court can use. Common challenges that Guardian ad Litem face are identified, with insights on how clinical sociological expertise can overcome them.